Handgrip Strength as an Indicator of Overall Strength and Functional Performance—Systematic Review - Piotr Szaflik; Hanna Zadoń; Robert Michnik; Katarzyna Nowakowska-Lipiec (Applied Sciences)
Reduced muscle strength can affect daily activities, so monitoring is essential. Methods such as isokinetic dynamometers assess maximum muscle force, while hand dynamometers measure hand grip strength. Research has investigated hand grip strength as a predictor of upper, lower and total strength, but the results remain unsystematic. The aim of this study was to systematize the current state of knowledge to test whether hand grip strength can be used as an indicator of overall strength and functional performance. A review of studies from 2000 to 2023 was conducted using: ScienceDirect, PubMed and GoogleScholar. The focus was on articles that examined the relationship between hand grip strength and muscle torque. The following keywords, entered in different configurations, were used in the search: ’hand grip’, ’muscle strength’, ’correlation’ and ’association’. A total of 22 studies were selected for analysis, involving 752 healthy adults, 30 physically active people, 120 ill adults, 2965 older people and 112 ill older people. The analysis looked at associations between hand grip strength and muscle moments of the trunk, limbs and knee joint. The results from the literature indicate that the value of the correlation between hand grip strength and muscle torque varies (from low to high) depending on the test method or group. Therefore, caution should be exercised when using hand grip strength as the sole measure of overall strength and functional performance.